PENGEMBANGAN POTENSI DAN PEMBERDAYAAN MASYARAKAT DESA MENDOYO DAUH TUKAD KABUPATEN JEMBRANA - I. K. A. Atmika; I. G. A. K. Suriadi (Buletin Udayana Mengabdi, 2016)
Mendoyo Dauh Tukad village located in the district Mendoyo, Jembrana Regency of Bali province, includingareas that have fertile land for agriculture with an average temperature of the village is 28o C - 30o C whichis good for a variety of crops. In addition to a potential agricultural area is also a great area to be used asbreeding areas to help improve the economy. Thus this village is a rural area that is fertile and rich inagriculture products, but everything is not fully utilized, therefore the necessary breakthrough to process thenatural resources. Gapoktan oyster mushroom cultivators constrained conditions of temperature and humidityin the mushroom house, so messelium do not grow well. Many straw that should be processed into animalfeed alternative. Livestock manure has the potential to be processed into organic fertilizer and biogas. The PENGEMBANGA POTENSI DAN PEMBERDAYAAN MASYARAKAT DESA MENDOYO DAUH TUKAD KABUPATENJEMBRANA98 | JURNAL UDAYANA MENGABDIpurpose of KKN PPM activities in the village Mendoyo Dauh Tukad is empowering communities inexploring the potential of the territory, to overcome the things mentioned above. Methods of implementationactivities are divided into three stages. The first stage is the preparation and debriefing, the second phase ofimplementation of activities in the field, and the third stage of evaluation and monitoring for correction andimprovement of the sustainability of the program. The preparation phase begins with the supervisor and thestudent court hearings with village officials and community leaders to determine the scale of priority actionsbased on the conditions and the potential that exists in the community, this event was held on July 92015.Tahap implementation of the activities carried out by counseling and practice in the field , as well asmentoring by students participating in service learning while in the field. Service activities carried out for onemonth starting on August 1, 2015 until August 30, 2015. The third phase is the evaluation and monitoring isdone by the implementation team or field supervisor and coordinator of corruption to see the impact andsustainability of programs that have been implemented.